An accurate solution to the nonlinear Lotka-Volterra equations by modified Homotopy Pertubation method - Chowdhury, Md. Sazzad Hossien (s.n, 2013)

(untitled)
In this works, we suggest a method to solve the nonlinear multispecies Lotka-Voltera equations. The suggested method, which we call modified homotopy perturbation method, can be considered as an extension of the homotopy perturbation method (HPM) which is very efficient in solving a varety of differential and algebraic equations. The HPM is modified in order to obtain the approximate solutions of Lotka-Voltera equation response in a sequence of time intervals